Animal Silk-Derived Amorphous Carbon Fibers for Electricity Generation and Solar Steam Evaporation - Qi, Ping; Ren, Jing; Ling, Shengjie (Frontiers in Chemistry, 2021)
Animal silks derived carbon materials are of interest to various applications, such as smart cloth and wearable sensors. However, it remains a challenge to transform silks into continuous carbon fibers massively. In this work, carbon fibers based on two kinds of aminal silks, i.e., Bombyx mori silk and Antheraea pernyi silk, are prepared by a large-scale-capable one-step heating process without any additives or activation process. These carbon fibers and yarns are electroconductive and mechanically robust. To expand the application of these carbonized silks, we further weaved them with cotton yarns to obtain composite fabrics with different textures and evaluated their performance for solar steam evaporation. Our results confirmed that the advantages of these composite fabrics in light absorption, large surface area, and hierarchical liquid transport channels allowed them to be used as a solar steam generation for desalination and sewage treatment. In addition, we reported that these conductive carbon fibers could be assembled into fluidic nanogenerators to generate electricity from flowing water. This work is expected to guide large-scale preparation and use of animal silks-derived amorphous carbon fibers.